Analisis Hubungan Antara Kasus Korupsi Harvey Moeis dan Setya Novanto serta Kaitannya dengan Hukum Tata Negara dan Undang-Undang NRI 1945 - Dian Permata Sari; Laila Fatia Maharani; Mila Agustin; Nourel Islamay Diandra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Corruption is an unlawful act that aims to enrich oneself, others, or a corporation, which in turn results in financial losses or has a negative impact on the country's economy. The definition of corruption itself is regulated in Law Number 31 Year 1999, which was later amended to Law Number 20 Year 2001. The harmful actions were committed by Harvey Moeis and Setyo Novanto. The losses incurred by each suspect were Rp 2.3 trillion and Rp 300 trillion, respectively. The writing method used in this article is literature study. This method can be done by collecting references consisting of several previous studies and then compiling them to draw conclusions. The corruption case committed by Harvey Moeis was related to the management of thyme commodity trading in Indonesian territory with a state loss of Rp 300 trillion, then the E-KTP case that dragged Setya Novanto's name. He is suspected of arranging for the project to be approved by the House of Representatives. Both cases violate Article 20A of Law Number 20 of 2001 and Law Number 31 of 1999 on the eradication of corruption. This case calls into question the accountability of public officials, especially in the case of Setya Novanto, the authority of state institutions over this case and the rule of law upheld in Indonesian constitutional law.